Correction: Robertson et al. Al3+ Modification of Graphene Oxide Membranes: Effect of Al Source. Membranes 2022, 12, 1237 - Ellen J. Robertson; Yijing Y. Stehle; Xiaoyu Hu; Luke Kilby; Katelyn Olsson; Minh Nguyen; Rebecca Cortez (Membranes)
The authors wish to make a correction to the published paper [...]